CHILD EDUCATION CONVENTION POLICY: IS PRIVACY ALTERNATIVE TO MEET QUALITY DEMAND? - Ribeiro dos Santos, Fernando Jose; Lara, Patricia Tanganelli [UNESP] (Unesp-faculdade Ciencias & Letras, 2020)
The study aims to to understand the processes of agreement in the municipal department of education of sao paulo and campinas to supply the demand for early childhood education, specifically in creches currently called the center for early childhood education (cei). In order to find solutions for the lack of vacancies in day care centers, the city of sao paulo and campinas opted for the partnership with private initiative. For data collection, scielo, google scholar and periodic capes databases were used. Of 18 articles surveyed, 6 were selected because they were relevant to the research question. The results pointed out that there are many obstacles to solving the problem and supplying the demand of children without access to school. The lack of quality of care in the agreed centers and the precarious training in the service of the education professionals, besides the inadequacy of physical space for the care of children.
Keywords: Child education; Covenants; Neoliberalism